Islamic Epistemology Studies of Children With Special Needs in Inclusion Education - Nikmah Rahmawati (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
This paper describes the epistemology of Islam in inclusive education. Education is a process of human development from stage to stage. This process develops the potential of each individual. To achieve this, education is equitable for all groups, including children with special needs. Seeing the social reality that occurs in the majority of the majority of people that children with special needs are much marginalized and often not even get love. The general view is that children who have disabilities are not useful in a social context. This is of particular concern to the government in special efforts to handle children with special needs in developing their potential. These efforts were implemented in the implementation of inclusive education. Inclusion education provides space for every human being, whether normal or disabled. In the view of Islam education is the duty of every human being. An Islam view that every human being is the same who distinguishes is the degree of piety. While physical differences are gifts from the creation. So in these context children with special or normal needs both have an obligation to undergo the education process to provide reinforcement on the understanding of inclusive education, this paper tries to examine, examine epistemologically. In particular the epistemology used is the epistemology of Islam. This is to explore where knowledge from inclusive education originates. The source of inclusion knowledge was used as a reinforcement of the importance of the implementation of inclusive education in the education model